2021
DOI: 10.1080/07352689.2021.1883826
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Unintended Risk in the Context of Old and New Breeding Techniques

Abstract: For thousands of years, humans have been improving crops to better suit their needs. These enhancements are driven by changes in the genetic makeup of the plant. While this was initially unintentional, there has been a steady push to increase the pace and precision of crop breeding, something that has occurred alongside a growing understanding of genetics and an escalating capacity to thoroughly assess genomes at the molecular level. With the advent and rapid uptake of molecular breeding techniques, such as tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 393 publications
(412 reference statements)
0
9
0
Order By: Relevance
“…Unfortunately, despite the potential of such genotypes for economic benefit, their implementation will almost certainly be hindered by their transgenic nature. Since crops developed using RNAi technology are considered to be “genetically modified” (“GM”), they would raise public concern and be subject to prohibitively costly and lengthy regulatory processes ( Singer et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, despite the potential of such genotypes for economic benefit, their implementation will almost certainly be hindered by their transgenic nature. Since crops developed using RNAi technology are considered to be “genetically modified” (“GM”), they would raise public concern and be subject to prohibitively costly and lengthy regulatory processes ( Singer et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unlinked nature of the resulting edit and the introduced transgene, this technology allows for the rapid production of non-transgenic germplasm bearing mutations that are identical in nature to those achieved spontaneously or through conventional breeding approaches such as chemical mutagenesis ( Subedi et al, 2020a , b ). While the regulatory status of crop varieties derived from genome editing is still uncertain in some countries, many others, including the United States, have concluded that in the absence of foreign DNA they are not “GM,” and will therefore not be subjected to costly and burdensome regulatory processes ( Schmidt et al, 2020 ; Singer et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Ionising radiations include X‐ray, γ‐rays, neutrons and high‐energy ion beams. Ionising radiations are the most commonly used physical mutagens (Mba, 2013 ; Navjot et al., 2018 ; Singer et al., 2021 ). Radiations are capable of dislodging electrons from the orbits of the atoms that they hit, transforming those atoms into ions.…”
Section: Assessmentmentioning
confidence: 99%
“…O4 alkylthymine, a lesion generated by ENU, can mispair with guanine and lead to A:T – G:C transitions. MMS, another important alkylating agent, induces the formation of N3 alkylguanine and N3 alkyladenine, leading to transversions or transitions (Leitao, 2012 ; Singer et al., 2021 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Mutations of this kind occur in plants at different rates depending on the genome size and ploidy. For example, in Arabidopsis thaliana, between 1 and 5 de novo intra-varietal mutations have been shown to occur per generation, whereas higher rates are found in rice and other plants with larger genomes (Singer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%